1982
DOI: 10.1073/pnas.79.17.5194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inactive form of fructose-1,6-bisphosphate aldolase isolated from livers of fasted rabbits.

Abstract: The accumulation of an inactive, immunologically crossreactive form offructose-1,6-bisphosphate aldolase (EC 3.1.3.11) in livers of fasted rabbits has now been related to limited proteolysis at the COOH terminus. The extent of modification of this region of the molecule, determined by analysis of tyrosine residues in the peptides released by digestion with subtilisin, agrees with the observed decrease in the specific activity of the enzyme purified from livers of fasted rabbits. The following evidence supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Treatment of liver aldolase with carboxypeptidase decreases the activity towards both hexose substrates by approx. 50 % [40,42] ; starvation-induced proteolysis of liver aldolase in mice, which also cleaves C-terminal residues, shows no selective effects on F-1-P activity [43]. Although the partly denatured Val$$( protein might be degraded more rapidly in i o compared with the wildtype enzyme, this would not explain the loss of function specific to aldolase B.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of liver aldolase with carboxypeptidase decreases the activity towards both hexose substrates by approx. 50 % [40,42] ; starvation-induced proteolysis of liver aldolase in mice, which also cleaves C-terminal residues, shows no selective effects on F-1-P activity [43]. Although the partly denatured Val$$( protein might be degraded more rapidly in i o compared with the wildtype enzyme, this would not explain the loss of function specific to aldolase B.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the starved rabbit, it was suggested that the inactive enzyme is a slightly truncated form derived from cathepsin M activity (20,21). A similar truncated form was found in the rat irradiated with x-rays and was attributed to cathepsin B activity (22,23).…”
Section: Discussionmentioning
confidence: 91%